Intracardiac echocardiography‐ versus transesophageal echocardiography‐guided left atrial appendage occlusion with Watchman FLX. (5th September 2021) - Gianni, Carola; Horton, Rodney P.; Della Rocca, Domenico G.; Mohanty, Sanghamitra; Al‐Ahmad, Amin; Bassiouny, Mohamed A.; Burkhardt, J. David; Gallinghouse, G. Joseph; Hranitzky, Patrick M.; Sanchez, Javier E.; Natale, Andrea
Abstract: Introduction: Watchman FLX has been recently approved for left atrial appendage occlusion (LAAO) in the US. Intracardiac echocardiography (ICE) ‐ which is already commonly used to guide trans‐septal access ‐ can serve as an alternative to TEE, simplifying the procedure and reducing associated costs. Herein, we report our experience with ICE‐guided LAAO with Watchman FLX. Methods and Results: This cohort study included the first 190 consecutive patients who underwent LAAO with Watchman FLX in our center. LAAO was successful in all patients without significant peri‐procedural, device‐related complications in either group. Compared to TEE, we observed a significant reduction in procedural times when using ICE. In addition, there was a potentially clinically relevant reduction in fluoroscopy dose, mainly secondary to fewer cine acquisition runs. At follow‐up, no cases of device embolism were noted, whereas the rate of device‐related thrombosis and peri‐device leaks were comparable between groups. Conclusion: ICE‐guided LAAO with Watchman FLX is safe and feasible, with a significant reduction in procedural time and potential reduction in fluoroscopy dose when compared to TEE.